A proposta de valor no MBA da Unisinos - Pires, Cibele Barbosa (Universidade do Vale do Rio dos Sinos, 2010)
This study aims at the evidence that there is an association of the value intention of the MBA of Unisinos and the students' perceived value of this sort of course. The classification of this study is research of applied nature, with qualitative and descriptive objectives, developed through a case study that analyses the MBA course of Unisinos in general, without focusing at any of the emphases offered. The answers obtained point to training, networking, recycling of knowledge, safety in professional practice and recognition of the course by the market as the main value intention of the institution. The result of the comparison of the value perception of the students, the responses show an alignment, although the course does not have complete information and understanding about the requests presented by students.
Keywords: MBA; Valor; Comparação de percepção; Value; Comparison of perception